Hadronic Production of Heavy QQ Bound States - Escobar, C. O.; Malbouisson, A. P.C.; Santoro, A. F.S.; Shellard, R. C.; Souza, M. H.G. (Wiley, 1981)
Several mechanisms for the production of heavy QQ bound states are reviewed. A systematic comparison between model predictions and experimental results is presented. The various theoretical and experimental uncertainties are discussed. Copyright © 1981 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim